Pengaruh kondisi Ekonomi, NPR, FDR Dan BOPO Terhadap Profitabilitas Perbankan Syariah Di Indonesia Tahun 2012-2015 - Ayu Ningrum, Anissa; Imronudin, S.E.,M.Si,Ph.D (2017)
The purpose of this study was to determine the effect of variable economic conditions (inflation and interest rates), the ratio of Non Performing Financing (NPF), Financing Deposit Ratio (FDR) and Operating Expenses Operating Income (BOPO) on the profitability of Islamic Banking in Indonesia. This paper describes the level of profitability is influenced by several factors, these factors are inflation, interest rate, NPF, FDR, and ROA, while the measuring instrument to assess the profitability of Islamic banking is the Return on Assets (ROA). This research used purposive sampling, the sample used in this research company sharia banking in Indonesia in 2012-2015 as many as 10 samples of Islamic Banks (BUS). Data analysis method used is the Multiple Linear Regression Analysis, Test The coefficient of determination (R2), F-statistics test, T-test and Classical Assumption Test. The results of this study indicate that inflation had no effect positive and significant on profitability (ROA). The Interest rate variable has no effect negative and significant on profitability (ROA). NPF had no effect significant negative on profitability (ROA). FDR had significant and negative effect on profitability (ROA). BOPO variabel had significant negative effect on profitability (ROA). The result of Coeficient Determination (R2) has a value of 0,793, so ROA can be explained by Inflation variable, Interest Rate, NPF, FDR and BOPO by 79,3% and remaining 20,7% is explained by factors or other variables outside the model. Keywords : Inflation, Interest Rate, NPF, FDR and BOPO